Comparative cephalometric evaluation of tongue position in subjects with skeletal class II division 1 and division 2 malocclusion - Shinde, Siddharth; Sethi, Shubhita; Vasa, Dhvaani; Bhosale, Veera; Patil, Krishna; Jadhav, Madhura (Journal of Orthodontic Science, 2023)
To evaluate and compare the position of the tongue from rest to centric occlusion in subjects with skeletal class II division 1 and skeletal class II division 2 malocclusions with subjects of skeletal class II normal occlusion. The study was conducted on 30 individuals equally divided into three groups of skeletal class II division (div) 1, skeletal class II div 2, and skeletal class I normal occlusion. The study was conducted on two lateral cephalograms for each subject: one taken at rest and one in centric occlusion. On evaluation of tongue posture, a statistically significant difference was observed at the middle portion of the tongue in class II div 1 malocclusion, and at the posteromedial portion of the dorsum of the tongue in class II div 2 skeletal malocclusions as the tongue moved from rest to centric occlusion. While statistically significant differences were found between class II div 2 malocclusion and class I normal occlusion, no statistically significant differences were observed between class II div 1 and class II div 2 malocclusions. Tongue position was observed to be the same in both class II div 1 and class II div 2 malocclusions, with no statistically significant differences. However, a great change was seen in the tongue position from rest to centric occlusion.